Genetic testing in professional football: perspectives of key stakeholders - McAuley, A. B.; Hughes, D. C.; Tsaprouni, L. G.; Varley, I.; Suraci, B.; Roos, T. R.; Herbert, A. J.; Kelly, A. L. (Journal of Science in Sport and Exercise, 2022)
Purpose: Genetic research in football is currently in it`s infancy but is growing rapidly. However, the practical application of genetic testing in football and the views concerning its use are unknown. Thus, the purpose of this study was to assess the current practical application of genetic testing in professional football and provide an insight into the perspectives of key stakeholders (i.e., coaches, practitioners, players). Methods: In total, 122 participants completed an online anonymous survey. This consisted of 21 multiple choice and Likert scale questions, with the option of providing an explanation for each response. Results: Findings revealed genetic testing is rarely utilised by key stakeholders (10%) or their respective organisations (14%). However, three quarters (75%) had the opinion that genetic testing will have great utility in the future. The majority (72%) believed genetic testing should be used for athlete development and injury risk, whilst 35% believed that genetic testing should be utilised for talent identification purposes. However, most key stakeholders viewed their own (89%) and their colleagues` (79%) knowledge related to genetic testing as insufficient; mainly due to ineffective current communication methods (91%). Most believed educational workshops are required (71%), whilst nearly all (91%) were interested in developing their expertise on the utility of genetic testing. Conclusion: Genetic testing is rarely used within professional football, although key stakeholders anticipate that it will be utilised more in the future. As such, educational support may prove valuable in improving key stakeholder knowledge and the practical application of genetic testing in professional football.